2007
DOI: 10.1016/j.jconrel.2007.06.014
|View full text |Cite
|
Sign up to set email alerts
|

PEG-b-PPA/DNA micelles improve transgene expression in rat liver through intrabiliary infusion

Abstract: We have developed a new block copolymer gene carrier that comprises of a polyethylene glycol segment and a degradable cationic polyphosphoramidate (PPA) segment. This PEG-b-PPA copolymer carrier formed micelles upon condensation with plasmid DNA in aqueous solution. PEG-b-PPA/DNA micelles exhibited uniform and reduced particle size ranging from 80 to 100 nm and lowered surface charge, compared with complexes of DNA with the corresponding cationic PPA carrier. PEG-b-PPA/DNA micelles maintained similar transfect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 36 publications
(54 reference statements)
2
45
0
Order By: Relevance
“…AFM micrographs of 3, coincubated with pBR322 plasmid DNA, revealed formation of irregular shaped structures suggesting interaction of DNA with carrier molecules as previously reported for DNA-micelle complexation [27] (Fig. 4A).…”
Section: Resultssupporting
confidence: 82%
“…AFM micrographs of 3, coincubated with pBR322 plasmid DNA, revealed formation of irregular shaped structures suggesting interaction of DNA with carrier molecules as previously reported for DNA-micelle complexation [27] (Fig. 4A).…”
Section: Resultssupporting
confidence: 82%
“…Chitosan and PEG-b-PPA were chosen because both had previously been shown to promote transgene expression while forming nanocomplexes. 454 In the fully formed complex, ET (E 12 ) proceeded from the QD donor (1) to the Cy3/BOBO-3 acceptors (2) and then (E 23 ) from Cy3/BOBO-3 (2) to Cy5 (3) as monitored by single particle characterization. Changes in FRET were used to monitor unpacking (reduction in E 23 ) and DNA degradation (reduction in E 12 ) within the complex.…”
Section: Kinases and Phosphatasesmentioning
confidence: 99%
“…( Dai et al, 2006;Jiang et al, 2007). The studies showed that there is a slight increase in serum AST and ALT activities at 1 day after infusion of plasmid DNA, followed by rapid decrease to the background level by day 3.…”
Section: Hsc-specific Hgf Delivery Retards Liver Fibrosis 517mentioning
confidence: 99%
“…The protocol for retrograde intrabiliary infusion was adapted from our previous work ( Jiang et al, 2007). Rats were anaesthetized with ketamine/xylazine, the common bile duct was canulated with a 32G needle (Hamilton), and a tie with 5-O silk sutures was placed to secure the needle.…”
Section: Retrograde Intrabiliary Infusionmentioning
confidence: 99%